2002
DOI: 10.4049/jimmunol.168.5.2508
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-γ Agonist 15-Deoxy-Δ12,1412,14-Prostaglandin J2 Ameliorates Experimental Autoimmune Encephalomyelitis

Abstract: Peroxisome proliferator-activated receptors (PPAR) are members of a nuclear hormone receptor superfamily that includes receptors for steroids, retinoids, and thyroid hormone, all of which are known to affect the immune response. Previous studies dealing with PPAR-γ expression in the immune system have been limited. Recently, PPAR-γ was identified in monocyte/macrophage cells. In this study we examined the role of PPAR-γ in experimental autoimmune encephalomyelitis (EAE), an animal model for the human disease m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
221
1
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(241 citation statements)
references
References 39 publications
15
221
1
4
Order By: Relevance
“…Moreover, administration of PPAR␥ ligands is reported to attenuate inflammation in murine models of inflammatory bowel disease (18), nonobese diabetic mice (19), rodent models of atherosclerosis (20 -22) and experimental allergic encephalomyelitis (EAE) (23,24). Studies performed in lymphocyte subpopulations have also confirmed the anti-inflammatory actions of the PPAR ligands (11,25).…”
mentioning
confidence: 66%
“…Moreover, administration of PPAR␥ ligands is reported to attenuate inflammation in murine models of inflammatory bowel disease (18), nonobese diabetic mice (19), rodent models of atherosclerosis (20 -22) and experimental allergic encephalomyelitis (EAE) (23,24). Studies performed in lymphocyte subpopulations have also confirmed the anti-inflammatory actions of the PPAR ligands (11,25).…”
mentioning
confidence: 66%
“…This PPAR-γ agonist also suppressed IFN-γ, IL-10, and IL-4 production by activated lymphocytes [12]. Administration of 15d-PGJ 2 at the onset of clinical disease significantly reduced EAE severity, supporting the potential clinical relevance of this treatment paradigm [12]. Feinstein et al [16] demonstrated that oral administration of thiazolidinediones including pioglitazone reduced the clinical severity of monophasic EAE, but it did not delay disease onset.…”
Section: Ppar-γ: Role In Eaementioning
confidence: 98%
“…Evidence to suggest that PPAR-γ agonists may potentially ameliorate MS was initially provided by Niino et al [36] who demonstrated that troglitazone inhibited the development of EAE. Diab et al [12] reported that the PPAR-γ agonist 15d-PGJ 2 inhibited the proliferation of neural antigen-specific T cells from the spleen of myelin basic protein Ac 1-11 TCR-transgenic mice, which spontaneously develop EAE. This PPAR-γ agonist also suppressed IFN-γ, IL-10, and IL-4 production by activated lymphocytes [12].…”
Section: Ppar-γ: Role In Eaementioning
confidence: 99%
See 1 more Smart Citation
“…Repression of fas-L expression in activated T cells might act in combination with the various effects mediated by 15d-PGJ 2 at the inflammatory site, in particular at the onset of autoimmune diseases in which local inflammation and tissue injury mediated by Th1 cytokines and Fas-L-mediated killing can generate specific tissue and organ damage. The recent description of in vivo studies that reveal a role for 15d-PGJ 2 as a molecule that may ameliorate inflammation in diseases such as EAE or IBD (15,18), together with the role mediated by Fas-L in these kinds of pathologies (23,71), suggest that modulation of this gene by 15d-PGJ 2 in T cells may represent an additional tool to consider for treatment of specific autoimmune and inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%